The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/cjoc.201900034
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Delivery Nanoparticles of Amphiphilic Acyclic Enediynes for Efficient Tumor Cell Suppression

Abstract: Summary of main observation and conclusion Four acyclic maleimide‐based enediyne compounds with different hydrophilicity were synthesized through Sonogashira reaction to reveal a self‐delivery antitumor drug platform. As proved by ESR analysis, the enediyne compounds undergo Bergman‐like cyclization and generate diradical intermediates at physiological temperature, which are able to induce DNA‐cleavage through the abstraction of H atoms from the sugar‐phosphate backbones. When the critical aggregation concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Meanwhile, the charge separation assistance in the metal‐ion‐catalyzed Bergman cyclization should not be excluded as well . Nevertheless, this study confirmed that the metalloenediyne EDY‐Cu is highly reactive towards spontaneous cycloaromatization at physiological temperature to produce free diradicals, endowing it with the ability of DNA cleavage and tumor cell suppression as discussed below.…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…Meanwhile, the charge separation assistance in the metal‐ion‐catalyzed Bergman cyclization should not be excluded as well . Nevertheless, this study confirmed that the metalloenediyne EDY‐Cu is highly reactive towards spontaneous cycloaromatization at physiological temperature to produce free diradicals, endowing it with the ability of DNA cleavage and tumor cell suppression as discussed below.…”
Section: Resultsmentioning
confidence: 50%
“…We also found that the cycloaromatization activities of the enediyne compounds could be regulated by simply adjusting the functional groups at the alkyne termini in order to realize the generation of free diradicals at low temperature . These maleimide‐based enediynes showed strong DNA‐cleavage and tumor cell suppression activities . Furthermore, substituent modifications at the maleimide moiety were applied in tailored synthesis of enediyne compounds employed in drug conjugates and drug delivery .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations